Managing soft skills development in vocational higher education: A case study of institutional practices in Indonesia - Syukri Fathudin Achmad Widodo; Sudji Munadi; Chrisna Tri Harjanto; Tri Adi Prasetya; Betania Kartika Muflih (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2025)
The demands of the workplace in the Industry 4.0 era require vocational education to produce graduates who not only master technical skills but also possess non-technical (or